Write the simplified expression: 2x + 3(x – 2) – 3(x -6)

Question

Write the simplified expression: 2x + 3(x – 2) – 3(x -6)

in progress 0
Vodka 2 months 2021-07-26T06:00:39+00:00 2 Answers 1 views 0

Answers ( )

    0
    2021-07-26T06:02:09+00:00

    Answer:

    2x+12

    Step-by-step explanation:

    2x+3(x−2)−3(x−6)

    Distribute:

    =2x+(3)(x)+(3)(−2)+(−3)(x)+(−3)(−6)

    =2x+3x+−6+−3x+18

    Combine Like Terms:

    =2x+3x+−6+−3x+18

    =(2x+3x+−3x)+(−6+18)

    =2x+12

    Answer:

    =2x+12

    0
    2021-07-26T06:02:24+00:00

    Answer:

    2x + 12

    Step-by-step explanation:

    distribute numbers inside parentheses

    2x + 3x -6 -3x + 18

    add x values together and integers together

    2x + 3x -3x = 2x

    -6 + 18 = 10

    simplified to 2x + 12

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )